2001
DOI: 10.1183/09031936.01.99109101
|View full text |Cite
|
Sign up to set email alerts
|

ABO/Secretor genetic complex and susceptibility to asthma in childhood

Abstract: A positive association has recently been reported in adult subjects between O/nonSecretor phenotype and asthma. To confirm this association, this study investigated the joint ABO/Secretor phenotype in a cohort of 165 asthmatic children. Three-hundred and sixty-two consecutive newborn infants from the same population were also studied as controls.The proportion of O/nonSecretor in asthmatic children was higher than in controls, thus confirming the association found in adults. The association was more marked in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 6 publications
4
25
1
1
Order By: Relevance
“…In asthma for example, the frequency of a non-secretor phenotype is higher among Caucasian asthmatics compared with non-asthmatics,34 however, within patients with asthma, those with a secretor genotype are more prone to exacerbations,26 analogous to the findings of this study. In COPD, patients who are non-secretors have a lower FEV 1 % compared with secretors 28.…”
Section: Discussionsupporting
confidence: 75%
“…In asthma for example, the frequency of a non-secretor phenotype is higher among Caucasian asthmatics compared with non-asthmatics,34 however, within patients with asthma, those with a secretor genotype are more prone to exacerbations,26 analogous to the findings of this study. In COPD, patients who are non-secretors have a lower FEV 1 % compared with secretors 28.…”
Section: Discussionsupporting
confidence: 75%
“…This Italian study showed an association between the O/non-secretor phenotype and childhood asthma. The difference was much more marked in males than in females (5). Another study determined the association between ABO, Lewis (Le), and secretor (Se) genetic complex and susceptibility to childhood asthma in Taiwan (10 (Se/Se) and O/Le(a-b-) were associated with childhood asthma (10).…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that claim that there is a significant relationship between a specific blood group and susceptibility to asthma or allergic rhinitis (4-6). Studies on adults and children with bronchial asthma have shown that asthma is significantly related to the O/non-secretor phenotype (4,5). Compared with controls, a significantly higher incidence of the O phenotype in male patients with allergic rhinitis was reported (6).…”
Section: Introductionmentioning
confidence: 99%
“…This observation is interesting, in particular with respect to previous studies on the link of FUT2 and respiratory illness (2,4,5), but this hypothesis needs to be evaluated in a prospective trial with larger cohorts.…”
Section: Discussionmentioning
confidence: 89%
“…About 80% of the Caucasian populations are secretors (either homozygous SeSe or heterozygous Sese) while the remaining 20% carry the homozygous 428G→A nonsense mutation in the FUT2 gene and are nonsecretors (sese). Several in vivo studies have revealed the clinical significance of this polymorphism and the secretor status in terms of susceptibility to infection and association with immunologically mediated diseases (1)(2)(3)(4)(5)(6). Thorven et al (1) were able to demonstrate that secretor-negative individuals are resistant to Norovirus infections possibly due to binding of Norovirus to secreted ABH histo-blood group antigens as indispensable condition for infection.…”
mentioning
confidence: 99%